DINAMIKA PERKEMBANGAN HUKUM KELUARGA DI INDONESIA - Fatah Hidayat (An Nisa'a, 2014)
Ups and downs of Islamic law development in Indonesian can be observed through their historical development. Various questions emerged dealing with this topic. Moreover, several studies and discussions on this topic had been done. They finally produced a conclusion, although some pro and contra responses occasionally appeared toward it. This article is expected to be a historical investigation to see the position of Islamic law in Indonesian state arrangement because in fact, it keeps developing and has a share in coloring the regulations prevailing in Indonesia.ملخص: كانت نشأة حكم العائلات فى اندونيسيا مناسبة بنشأة الإسلام نفسه. فأوّلا، المواصلات بين المجتمع الأصلى وتجّار المسلمين تصنع "صيغة" ثقافة أو معاملة جديدة فى المجتمع. وكذلك احكام العائلية الإسلامية. ستبحث هذه المقالة عن نشر حكم الإسلام وتجديده فى اندونيسيا وهى ستستعمل اربعة مراحل مناسبة بالمرحلة الكبرى من معلوم تاريخ نشأة اندونيسيا. وأمّا الغرض الذى سيوجد فهو "الى أيّ حدّ استعمل حكم العائلة الإسلامية فى قانون العائلات باندونيسيا.